Geopolítica e integração regional: uma análise dos projetos de infraestrutura de transportes entre Brasil e Paraguai - Oliveira Cruz, Dayana Aparecida Marques de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
A relação assimétrica e desigual entre Brasil e Paraguai na América do Sul demonstra a complexidade do subsistema regional, que deve ser lida não só a partir do contexto econômico, mas também do contexto (geo) político regional, associado por sua vez ao sistema-mundo. Se por um lado, a ampliação da exportação de commodities e dos acordos de integração regional demandam o planejamento e investimento em projetos de infraestruturas, sobretudo de transportes; por outro lado, a fragilidade institucional e financeira dos acordos regionais contribui para o atraso no cronograma de execução desses projetos. A partir da análise do processo de integração regional sul-americano, considerando o Mercado Comum do Sul (MERCOSUL), o Conselho Sul-americano de Infraestrutura e Planejamento/Iniciativa para a Integração da Infraestrutura Regional Sulamericana (COSIPLAN/IIRSA), e o papel de liderança desempenhado pelo Brasil, afirmamos que existe uma estreita relação entre integração regional e geopolítica, na qual os projetos internacionais de infraestruturas podem ser considerados como pontos de encontro entre ambos.

The asymmetric and unequal relationship between Brazil and Paraguay in South America demonstrates the complexity of the regional subsystem, which must be read not only from the economic context, but also from the regional (geo) political context, associated in turn with the world system. If, on the one hand, the expansion of commodities exports and regional integration agreements demand planning and investment in infrastructure projects, especially transportation; on the other hand, the institutional and financial fragility of the regional agreements contributes to the delay in the execution schedule of these projects. Based on the analysis of the South American regional integration process, considering the Southern Common Market (MERCOSUL), the South American Council on Infrastructure and Planning / Initiative for the Integration of Regional South American Infrastructure (COSIPLAN / IIRSA), and the leading role played by Brazil, we affirm that there is a close relationship between regional and geopolitical integration, in which international infrastructure projects can be considered as meeting points between the two.
Geopolitics and regional integration: an analysis of transport infrastructure projects between Brazil and Paraguay
Keywords: Integração regional; Geopolítica; Projetos de infraestruturas de transportes; Brasil; Paraguai; Regional integration; Geopolitics; Transport infrastructure projects; Brazil; Paraguay